1983
DOI: 10.1210/jcem-56-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cytosol Androgen Receptor of the Human Prostate*

Abstract: Direct measurement of the binding of endogenous androgens to the androgen receptor of human tissues has not been possible because of contamination of tissue with traces of plasma proteins, such as testosterone-binding globulin (TeBG), that contain more androgen-binding capacity than does the receptor itself. Molybdate is known to stabilize the 8-9S forms of other steroid hormone receptors. We took advantage of this phenomenon to characterize the androgen receptor of hyperplastic prostates removed at surgery, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(50 citation statements)
references
References 46 publications
1
47
0
2
Order By: Relevance
“…Under these conditions, it made no difference whether the samples were incubated for 1 h (shorter periods were not examined) or 24 h before applying them to density gradients (results not shown). As previously reported for human prostate (16) and foreskin (1 1-13), freezing the tissue in liquid nitrogen for as long as 3 d had no effect on the receptor levels (Table I). Methyltrienolone was used as the binding ligand because it is not metabolized at a significant rate by either cytosol or nuclear extracts (results not shown) and because it binds weakly to testosterone-binding globulin of plasma.…”
Section: Resultssupporting
confidence: 80%
“…Under these conditions, it made no difference whether the samples were incubated for 1 h (shorter periods were not examined) or 24 h before applying them to density gradients (results not shown). As previously reported for human prostate (16) and foreskin (1 1-13), freezing the tissue in liquid nitrogen for as long as 3 d had no effect on the receptor levels (Table I). Methyltrienolone was used as the binding ligand because it is not metabolized at a significant rate by either cytosol or nuclear extracts (results not shown) and because it binds weakly to testosterone-binding globulin of plasma.…”
Section: Resultssupporting
confidence: 80%
“…In some, but not all studies, a correlation has been found between T replacement therapy, and an increased risk of prostate cancer in men (Marks et al 2006). Development of prostate cancer often results from abnormal activation of ARs, which can be precipitated by circulating androgen levels (Guerini et al 2005), in particular DHT because of its greater affinity for ARs than T, especially in the prostate (Grino et al 1990;Kaufman and Pinsky 1983;Wilbert et al 1983). As such, therapeutics often prescribed for some types of prostate cancer include finasteride, to prevent binding of DHT to those abnormal ARs (Rittmaster 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that variation in the genes involved in androgen biosynthesis and metabolism may be risk factors for prostate cancer (12). One of these genes is steroid-5-α-reductase, which irreversibly catalyzes the conversion of testosterone to its more active and most potent androgen DHT (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to catalysis of this enzyme, the binding affinity of DHT to an androgen receptor is five times higher compared with that of testosterone (13). It has been demonstrated that young Japanese males have a lower steroid-5-α-reductase activity compared with young Caucasian-American and African-American males (15), and the DHT:testosterone ratio was highest in African-Americans, intermediate in Caucasians and lowest in Asian-Americans, corresponding to the respective risk of developing prostate cancer in these groups (16,17).…”
Section: Introductionmentioning
confidence: 99%